Non-covalent interactions involving remote substituents influence the topologies of supramolecular chains featuring hydroxyl-O–H⋯O(hydroxyl) hydrogen bonding in crystals of (HOCH2CH2)2NC(S)N(H)(C6H4Y-4) for Y = H, Me, Cl and NO2 - Tan, Sang Loon *; Tiekink, Edward R. T. * (Royal Society of Chemistry, 2021)
Crystallography shows the universal adoption of supramolecular chains featuring hydroxyl-O–H⋯O(hydroxyl) hydrogen bonding in crystals of (HOCH2CH2)2NC([double bond, length as m-dash]S)N(H)(C6H4Y-4) for Y = H (1), Me (2), Cl (3) and NO2 (4). However, distinct topologies, i.e. linear (Y = H), helical (Y = Me and Cl) and zig-zag (Y = NO2) are noted with major differences in the pitch of the polymer. Geometry-optimisation, MEP and NPA analyses show a distinct electronic structure for the Y = NO2 derivative, in particular relating to the activation of the aryl ring. An exhaustive analysis of the molecular packing (point-to-point interactions, crystal structure similarity, Hirshfeld surface analysis, NCI and QTAIM, interaction energies and energy frameworks) points to the importance of C–H⋯π(aryl) interactions in stabilising the chains but these have a considerably reduced influence in the crystal with Y = NO2 (4), where π(aryl)⋯π(aryl) interactions are important. The more open arrangement for the linear chain in 1 facilitates the formation of C–H⋯π(aryl) interactions and the more compact arrangements enable the formation of stabilising, intra-chain methylene-C–H⋯S(thione) interactions 2–4. This study highlights the role of second-tier non-covalent interactions in the arrangement of conventional hydrogen bonding interactions.